Efficacy of low-dose vaginal 17β-estradiol versus vaginal promestriene for vulvovaginal atrophy. (4th July 2022) - Palacios, S.; Ramirez, M.; Lilue, M.
Abstract: Objective: Vulvovaginal atrophy is frequent, can be bothersome and can impair quality of life in postmenopausal women. The main objective of this prospective, randomized study was to compare the acceptability of low-dose vaginal 17β-estradiol (estradiol) tablets and vaginal promestriene cream in postmenopausal women with moderate-to-severe symptomatic vulvovaginal atrophy. Methods: Overall, 120 patients were randomized to receive estradiol or promestriene ( n = 60 per group). Acceptability was assessed with a specific questionnaire. Symptom intensity, the Vaginal Health Index (VHI), vaginal pH and the Vaginal Maturation Index were also evaluated. Results: Acceptability was higher for estradiol tablets. Compared to promestriene cream, hygiene and ease of use were greater after 4 weeks ( p = 0.011 and p = 0.001, respectively) and after 12 weeks ( p = 0.009 and p = 0.011, respectively). Reduction of symptom intensity was greater with estradiol. Both treatments improved the VHI and decreased vaginal pH. However, superficial cell percentages increased significantly ( p < 0.001) with estradiol but not with promestriene ( p = 0.241), with a statistically significant difference between means ( p = 0.004). Conclusion: Our results support the use of vaginal low-dose estradiol tablets as compared to vaginal promestriene cream for the management of moderate-to-severe symptomatic vulvovaginal atrophy in postmenopausal women. ClinicalTrials.gov Identifier: NCT04232813